Questioning Bourdieusian Symbolic Violence on Lesbian Characters in Ayu Utamis Saman and Djenar Mahesa Ayus Nayla - Fahruddin F; Desca Angelinawati (Indonesian Journal of English Language Studies (IJELS), 2019)
LGBTIQ has become a controversial topic concerning ones sexual preference over the past few years in Indonesia. Indonesian sexuality will always intersect with the norms, religious values and the state laws. Therefore, this phenomenon is socially binding as it restricts the identity construction of differing sexual preferences in Indonesia. The issue about sexuality particularly LGBTIQ is addressed in several Indonesian literature, given the significant and notable increase in Indonesian novels with LGBTIQ themes since 2000s. Taking the novels of Ayu Utamis Saman and Djenar Mahesa Ayus Nayla as the objects of investigation, this study examines (1) how Bourdieusian symbolic violence is being questioned in the novels (2) how these novels also challenge the hetero-normativity in Indonesia. The study reveals the symbolic violence towards the lesbian characters in the selected novels through the process of normalisation. However, by raising the issues of lesbianism, the novels and their circulation can somehow be seen as a form of resistance towards the Indonesian homophobic society.Keywords: symbolic violence, Indonesian novels, lesbianism, heteronormativity